On the Origin and Status of the "El Greco Fallacy". (June 2013) - Firestone, Chaz
The oddly elongated forms painted by the Spanish Renaissance artist El Greco are popularly but incorrectly attributed to astigmatism. The particular reason this explanation fails has long offered a deep lesson for perceptual psychology, even motivating recent research. However, the details and historical origins of this lesson—often called the "El Greco fallacy"— have been obscured over many retellings, leading to an incomplete and even inaccurate understanding of its provenance and status. This note corrects the record, which is richer, subtler, and more interesting than recent accounts would suggest.